Synthesis and Coordination Chemistry of a New N-4-Polydentate Class of Pyridyl-Functionalized Scorpionate Ligands: Complexes of Fe-II, Zn-II, V-IV, Pd-II and Use for Heterobimetallic Systems - Wanke, Riccardo (2011)
The new potentially N-4-multidentate pyridyl-functionalized scorpionates 4-((tris-2,2,2-(pyrazol-1-ypethoxy)methyl)pyridine (TpmPy, (1)) and 4-((tris-2,2,2-(3-phenylpyrazol-1-yl)ethoxy)methyl)pyridine (TpmPy(Ph), (2)) have been synthesized and their coordination behavior toward Fe-II, Ni-II, Zn-II, Cu-II, Pd-II, and V-III centers has been studied. Reaction of (1) with Fe(BF4)(2)center dot 6H(2)O yields [Fe(TpmPy)(2)](BF4)(2) (3), that, in the solid state, shows the sandwich structure with trihapto ligand coordination via the pyrazolyl arms, and is completely low spin (LS) until 400 K. Reactions of 2 equiv of (1) or (2) with Zn-II or Ni-II chlorides give the corresponding metal complexes with general formula [MCl2(TpmPy*)(2)] (M = Zn, Ni; TpmPy* = TpmPy, TpmPy(Ph)) (4-7) where the ligand is able to coordinate through either the pyrazolyl rings (in case of [Ni(TpmPy)(2)Cl-2 (5)) or the pyridyl-side (for [ZnCl2(TpmPy)(2)] (4), [ZnCl2(TpmPy(Ph))(2)] (6) and [NiCl2(TpmPy(Ph))(2)] (7)). The reaction of (1) with VCl3 gives [VOCl2(TpmPy)] (8) that shows the N-3-pyrazolyl coordination-mode. Moreover, (1) and react with cis-[PdCl2(CH3CN)(2)] to give the disubstituted complexes [PdCl2(TprnPy)(2)] (9) and [PdCl2(TpmPy(Ph))(2)] (10), respectively, bearing the scorpionate coordinated via the pyridyl group. Compounds (9) and (10) react with Fe(BF4)(2) to give the heterobimetallic Pd/Fe systems [PdCl2(mu-TpmPy)(2)-Fe](BF4)(2) (11) and [PdCl2(mu-TpmPy(Ph))(2)Fe-2(H2O)(6)]BF4)(4) (13), respectively. Compound (11) can also be formed from reaction of (3) with cis-[PdCl2(CH3CN)(2)], while reaction of (3) with Cu(NO3)(2).2.5H(2)O generates [Fe(mu-TpmPy)(2)-Cu(NO3)(2)](BF4)(2) (12), confirming the multidentate ability of the new chelating ligands. The X-ray diffraction analyses of compounds (1), (3), (4), (5), and (9) are also reported.